2010
DOI: 10.1542/peds.2009-3464
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Care Training of Midwives and Neonatal and Perinatal Mortality Rates in a Developing Country

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The majority of infant deaths occur during the neonatal period. Educational programs available to train neonatal health care workers are effective in improving knowledge and skills, but there are limited data on their effects on neonatal mortality rates. WHAT THIS STUDY ADDS:Training midwives in neonatal care reduces early neonatal mortality rates for infants born in lowrisk, first-level facilities. abstract + OBJECTIVE: This study was designed to test the hypothesis that 2 trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 18 publications
3
117
0
1
Order By: Relevance
“…The pre-ENC and post-ENC populations were comparable, as reported in a previous publication. 9 This population comprised 98% of all the neonates born with low-risk institutional deliveries in the 2 cities. All-cause 7-day neonatal mortality decreased from 11.5 per 1000 to 6.8 per 1000 after ENC training (relative risk: 0.59; confidence interval: 0.48 -0.77; P Ͻ .001) and was associated with a decrease in deaths caused by birth asphyxia (3.4 -1.9 per 1000; P ϭ .02) and infection (2.1-1.0 per 1000; P ϭ .02).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pre-ENC and post-ENC populations were comparable, as reported in a previous publication. 9 This population comprised 98% of all the neonates born with low-risk institutional deliveries in the 2 cities. All-cause 7-day neonatal mortality decreased from 11.5 per 1000 to 6.8 per 1000 after ENC training (relative risk: 0.59; confidence interval: 0.48 -0.77; P Ͻ .001) and was associated with a decrease in deaths caused by birth asphyxia (3.4 -1.9 per 1000; P ϭ .02) and infection (2.1-1.0 per 1000; P ϭ .02).…”
Section: Resultsmentioning
confidence: 99%
“…9 This cost analysis documents the cost-effectiveness and relatively low cost of the ENC educational intervention compared with other interventions aimed at reducing neonatal mortality in developing countries.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, room air resuscitation can reduce neonatal mortality 29 and has been done without oxygen blending in large clinical studies. 30,31 In clinical studies, hypopharyngeal oxygen concentrations have been shown to be reliable measures of the actual inspired oxygen concentrations. [32][33][34][35][36][37][38] If hypopharyngeal oxygen concentrations need to be decreased from those achieved with the 100% oxygen source, an entrainment device would be useful in those situations.…”
Section: Figurementioning
confidence: 99%